PERBANDINGAN LATIHAN PLIOMETRIK DEPTH JUMP DAN JUMP TO BOX POWER TERHADAP OTOT TUNGKAI DALAM SMASH PERMAINAN BOLA VOLI - Suprianti, Deswita; Paripurna, Zenda (STKIP Pasundan, 2017)
This study aims to find out better plyometric exercises between depth jump and jump to box plyometrics exercises on leg muscle power in volleyball smash games in Mts Salafiah extracurricular. This research uses experimental methods with the design of